Physical and chemical analysis in crude taro mucilage obtained by simple extraction technique - Andrade, Luan Alberto; Nunes, Cleiton Antônio; Pereira, Joelma (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2021)
Crude taro mucilage (CM) is considered a product that contains the presence of starch, in addition to other carbohydrates. The use of this mucilage is interesting in the bakery industry, mainly as an emulsifier. The objective of this study was to understand the chemical and physical characteristics of CM to justify its emulsifying action and find other potential applications in the food industry. In the first stage of the work, the raw material (taro rhizome) used for the extraction of mucilage was chemically characterized (moisture, ether extract, crude protein, crude fiber, ashes and glicidic fraction). CM was extracted through a simple method and without the use of chemical reagents, using rhizome crushed, filtration on a polyester mesh and lyophilized. Proximate composition, starch, minerals, monosaccharides, amino acids, infrared spectrum, X-ray diffractometry and thermal property analyses were conducted in the mucilage. CM has thermal stability up to approximately 200 °C and has semi-crystalline structure. Mucilage studied contains arabinogalactan polysaccharide, which can be linked to the protein fraction, according to infrared analysis, forming the arabinogalactan-protein macromolecule, responsible for the emulsifying property. The starch found is considered the main responsible for its thickening action. Moreover, CM can be considered mineral-enriching flour in food products due to the increase of ashes by the mucilage extraction process and the high content of iron micromineral.